The Cultivation of Junior Middle School Students' Problem Awareness under the Background of Mathematics Core Literacy - Hua, Xiujuan; Zhao, Yige; Sun, Shurong; Han, Zhenlai (International Journal of Educational Studies, 2018)
Learning from thinking, thinking from doubt, People's thinking begins with problems, and they think only when they have problems. As a hot spot of educational research nowadays, the core accomplishment of mathematics leads the new direction of educational reform, puts forward higher requirements for solving mathematical problems, and pays more attention to cultivating students to solve mathematical problems with the thinking of core literacy of mathematics. Through discussing the meaning of mathematics core accomplishment and the recognition of "problem solving" under the background of mathematics core accomplishment, this paper discusses three methods of cultivating students' problem consciousness: creating situation, arousing problem consciousness, making students want to ask questions; The democratic atmosphere, the cultivation self-confidence, causes the student dares to ask; the positive appraisal, the body Test the sense of achievement, make the students happy to ask, so as to arouse teachers pay attention to cultivating students' problem awareness and ability, and stimulate students' creative thinking.